2020
DOI: 10.1021/acs.jchemed.9b01166
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Applications of Metal–Organic Frameworks (MOFs): A Laboratory Activity and Demonstration for High School and/or Undergraduate Students

Abstract: The chemistry of metal–organic frameworks (MOFs), a new class of emerging crystalline porous solids with three-dimensional (3D) networks composed of metals and multidentate organic molecules, was introduced by using three differently shaped crystals. We reported new and mild MOF synthesis methods that are simple and devised to be performed in high school or primarily undergraduate school settings. MOF applications were demonstrated by use of our synthesized MOFs in the capture of iodine as a potentially hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
0
35
0
3
Order By: Relevance
“…However, because of the time limitation, commercial ZIF-8 was provided to the students instead. It is worth mentioning that another colorful substance such as iodine can also be used as the guest to demonstrate the adsorption ability of ZIF-8 . ZIF-8 exhibits an effective pore size of 3.4 Å, which is smaller than the size of MB molecules (24.2 Å × 14.8 Å, Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the time limitation, commercial ZIF-8 was provided to the students instead. It is worth mentioning that another colorful substance such as iodine can also be used as the guest to demonstrate the adsorption ability of ZIF-8 . ZIF-8 exhibits an effective pore size of 3.4 Å, which is smaller than the size of MB molecules (24.2 Å × 14.8 Å, Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al proposed an ultrasonic-assisted method for the synthesis of HKUST-1 (HKUST = Hong Kong University of Science and Technology) with a highlight on green and sustainable chemistry . Very recently, Sakamaki et al reported the mild synthesis of a series of MOFs, including MOF-5, ZIF-8, and MIL-101 (Fe) (MIL = Materials of Institute Lavoisier) and applied them to iodine capture and drug encapsulation . These good examples have provided insightful guidance on how to introduce MOFs in undergraduate or high school laboratory classes.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry content that was the focus of the video dealt with metal–organic frameworks (MOFs), as this is the main focus of one area of the author’s scholarly research. MOFs are microscopic particles with large surface areas that are porous and can be used therefore in the adsorption of certain target chemicals and/or to deliver target chemicals stored within them to specific active sites often for medical purposes. Additionally, these substances are crystalline in nature and as such hold very specific molecular geometries that can be viewed via transmission electron microscopy (TEM) and scanning electron microscopy (SEM), the latter of which produces nice three-dimensional images. Figure displays the synthesis process and chemical structures for the MOFs utilized in this project.…”
Section: Designmentioning
confidence: 99%
“…22 Compared to conventional electrode materials, MOF-based electrodes have gained prominence as an emergent class of porous crystalline materials due to their fascinating structural features, high porosity, varied architectures, and tailored functionalities. 25 MOFs have found their widespread application in gas storage systems, 26 aqueous energy devices, 20,27–31 catalysis, 32 and so on.…”
Section: Introductionmentioning
confidence: 99%